Soil Erosion Evaluation and Mapping Based on Geomatic Techniques in Wadi El Malleh Watershed - El Garouani, Abdelkader; EID, Asmaa Nasser Mohamed; El Aroussi, Omar (European Scientific Journal, ESJ, 2017)
Soil erosion by water considered is serious problem in the Mediterranean region due to the climate aggressiviness of the mountainous terrain, the traditional farming practices and other anthropogenic pressure on its land and soil. The present study was scheduled to use Geographical Information System (GIS), Remote Sensing data and the Revised Universal Soil Loss Equation (RUSLE) model to evaluate the annual average soil loss and sedimentation rate from Wadi El Malleh watershed, which is located in the Northern-Fez (Morocco), and covers an area of 34 km2 . In fact, RUSLE and SEDIMENTATION models were combined with GIS techniques to predict the spatiotemporal distribution of soil erosion and deposition under different land uses. The land use was assessed using the Google Earth image, which was taken in 2013. The image was first geo-referenced and projected into Moroccan coordinates system and classified by ArcGIS software. The use of RUSLE model allowed the estimation of static soil loss. Then the results of RUSLE were applied in the deposition modelling calculations to assess the spread of soil loss downstream by SEDIMENTATION model. The values of the annual net soil erosion obtained by this study were (81.86 t/ha/y) in bad land, (-19.19 t/ha/y) in irrigated agriculture areas and (-13.66 t/ha/y) in reforestation land where the negative values indicated deposition.